Analysis of Dinucleotide Bias and Genomic Signatures Across Cyanobacterial Genomes - P. Singh, Dhananjaya; Prabha, Ratna (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Dinucleotide relative abundance or frequency of dinucleotides in particular nucleotide sequence is reported as genomic signature as it is specific across different DNA samples and able to identify the variance among different groups whereas identical or similar for closely related organisms. Dinucleotide relative abundance value is identified to be overall constant due to numerous factors as dinucleotide stacking energy and DNA helicity, mechanisms of replication, repair and context-dependent mutation pressures and includes information about genome-wide processes. In this study, we analyzed genome sequence of 41 cyanobacteria to gain an insight of dinucleotide bias in their genomes. Across different dinucleotides, TA is broadly underrepresented followed by CG and then AC+GT whereas; AA+TT and GC occupied a major portion of dinucleotide distribution across all cyanobacterial genomes. Underrepresentation of TA seems to be influenced by GC-content of the members as it tends to decrease when there is an increase in GC content. Members with similar GC content possess similar pattern of genomic signature. Habitats also seem to influence the dinucleotide relative abundance values of the organisms because it is suggested that marine organisms.